Is It Time to Reconsider Rituximab Dosing Regimens for Pemphigus Vulgaris? - Christian Ciolfi; Jacopo Tartaglia; Mauro Alaibac (Antibodies, 2024)
Rituximab is currently approved for patients affected by moderate-to-severe pemphigus vulgaris, a severe autoimmune blistering skin disease that can be life-threatening. The standard rituximab dosing regimens, originally established for B-cell non-Hodgkin’s lymphomas, have been recognized to exceed the effective dose required for inducing B-cell depletion, considering that the B-cell burden in pemphigus vulgaris is considerably lower than in lymphoproliferative disorders. We herein report our experience with very ultra-low-dose rituximab in two patients affected by pemphigus vulgaris.